(3cJGH CYdGe GdfUQ GdeHjf aj GdeaGVdI Hjf Cgdi Uajfs - (3GHf gHI GdcdHjs
(3ChdgG (B:s
(3CeG HYO MeO Gddg HbOQ GdMjGI hGdBLd aEfc SCdJfi CYR Gddg fUQc Yf CNHGQ MQH Uajf heG LQ ajg Hjf GdeSdejf GdeNJdajf s
(3BNQgG (B:s
(3hfMf fbhd ceG CeQfG Gddg GdYXje QHfG CZaQ dfG hdENhGffG GdPjf SHbhfG HGdEjeGf hdGJLYd ai bdhHfG ZdkG ddPjf BefhG QfHG Efc QDha QMje BNQ GdcJGH hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs